The effect of organisational structure on quality management in public hospitals in a developing nation: a comparative study between district, state and national level hospitals in Malaysia - Abd. Manaf, Noor Hazilah (Korean Society for Quality Management, 2006)
The objective of the study was to empirically assess the practice of quality management among employees of Malaysian public hospitals at the district, state and national level hospitals. Comparative analysis on the practice of quality management was made among the three groups of hospitals. Self-administered questionnaire was the main method of data collection. Twenty-three public hospitals throughout Peninsular Malaysia participated in the survey. Practice of quality management was found to be significantly higher in district hospitals than in the national referral centre, which is based in the capital city of Kuala Lumpur. However, there was no significant difference in perception of implementation outcome between the three levels of hospitals. Among the factors of quality management, teamwork was found to be significantly higher in district hospitals than in state hospitals and the national referral centre. Leadership and management commitment was found to be significantly higher in district and state hospitals than in the national referral centre. The effect of organizational structure could have an effect on practice of quality management.